High platelet reactivity on aspirin in patients with acute ST elevation myocardial infarction. Issue 144 (August 2016) - Dillinger, Jean-Guillaume; Saeed, Alaa; Spagnoli, Vincent; Sollier, Claire Bal dit; Sideris, Georgios; Silberman, Stephane Manzo; Voicu, Sebastian; Drouet, Ludovic; Henry, Patrick
Abstract: Background: Despite dual antiplatelet treatment, major ischemic events are common following ST elevation myocardial infarction (STEMI). We aimed to assess high platelet reactivity on aspirin (HPR-aspirin) and its association with P2Y12i (HPR-P2Y12i) during the acute phase of STEMI. Methods: We included all consecutive patients admitted for STEMI treated by primary angioplasty in our center for 1 year. All patients received a loading dose followed by a maintenance dose of aspirin (75 mg/day) and prasugrel (ticagrelor or clopidogrel if contraindicated). Platelet reactivity was assessed 4 ± 1 days and 75 ± 15 days after admission using light transmission aggregometry with arachidonic acid (LTA-AA–HPR-aspirin) and VASP (HPR-P2Y12i) to define HPR as well as serum Thromboxane-B2 and LTA-ADP. Major cardiac and cerebrovascular events were recorded for 1 year. Results: We included 106 patients – mean age was 61 y.o., 76% were male and 20% had diabetes. STEMI was anterior in 52% and LV ejection fraction at discharge was 51 ± 9%. 50% of patients were treated with prasugrel and 34% with ticagrelor. At day 4 after STEMI, HPR-aspirin was found in 26% patients and HPR-P2Y12i in 7%. HPR- both aspirin and P2Y12i was found in 4%. Diabetes and age were predictors of HPR-aspirin. HPR-aspirin was persistent 75 days later in 36% patients. At 1 year, 7.9% patients had experienced major adverse cardiovascular and cerebrovascular events (MACCE). HPR-aspirin and HPR on both aspirin and P2Y12i were significantly associated with MACCE. Conclusion: HPR-aspirin is frequent just after STEMI and associated with MACCE especially when associated with HPR-P2Y12i. Highlights: What is known about this topic? Acute cardiovascular events including stent thrombosis are frequent after acute myocardial infarction Drug interaction, problems of absorption or unstable hemodynamics could lead to a decrease in effectiveness of antithrombotic therapy High platelet reactivity on aspirin and P2Y12i have never been studied in acute myocardial infarction What does this paper add? HPR-aspirin is frequent at the acute phase of myocardial infarction (23%) HPR-aspirin alone and HPR on both aspirin and P2Y12i are significantly associated with MACCE The occurrence of HPR-aspirin decreases over time following the acute event